Effect of Electroacupuncture at Changqiang Acupoint on Learning and Memory Ability and Hippocampal CA1 Apoptosis in Rats with Vascular Dementia - Ke'ai CHEN; Ping YU; Jie CHEN; Lianhong HUANG; Wei XU (康复学报)
Objective:To observe the effect of electro-acupuncture (EA) at Changqiang (GV1) acupoint on the learning and memory ability and hippocampal CA1 cellular apoptosis in rats with vascular dementia (VD).Methods:Sixty male SD rats according to the Morris water maze test were divided into three groups: 9 rats for blank control group, 9 rats for sham-operated group and 42 rats for surgical control group. Rats of VD models were established by 2 vessels obstruction (2-VO), 27 rats were selected from the surgical control group and divided into three groups: 9 rats for model group, 9 rats for EA treatment group and rest 9 rats for the non-acupoint EA control group. After the treatment, the water maze test and the TUNEL test were examined.Results:Compared with the model group, the escape latent period and the CA1 apoptosis of the blank control group and the EA treatment group were apparently shorter (P<0.05), and the times of crossing the platform were significantly increased (P<0.05). A positive correlation between CA1 apoptosis and latent period was identified (P<0.05), a negative correlation between apoptosis and the times of crossing was identified (P<0.05).Conclusion:EA at Changqiang acupoint may improve the learning and memorizing ability and restrain the apoptosis of hippocampal CA1 region of VD rats, and association of the ability and apoptosis is positive.